Design of bionic locust mouthparts stubble cutting device - Zhao, Jiale; Guo, Mingzhuo; Lu, Yun; Huang, Dongyan; Zhuang, Jian (International Journal of Agricultural and Biological Engineering, 2020)
Given the technical problems of low maize stubble breaking efficiency, large cutting torque and high power consumption faced during springtime no-till planting in Northeast China, we designed a high-performance coupling bionic stubble cutting device capable by integrating the structure (multi-segment and serrate) and cutting mode (isokinetic and symmetrical) of locust mouthparts. Methods of bionic construction, mechanism design, theoretical analysis, parameter optimization, Arduino systems and intelligent control were combined to design a planetary gear mechanism and an intelligent speed control system. In particular, the bionic cutting blade could reconstruct the multi-segment and serrate structure of locust mouthparts, while the planetary gear mechanism and the intelligent speed control system jointly comprised the bionic drive system, which could simulate the isokinetic and symmetrical cutting mode, thereby bionically coupling morphological structures and movement patterns. Analysis of comparative tests showed the coupling bionic cutting device could reduce the cutting torque by 26.6%-31.6% and the power consumption by 21.9%-26.1%. This work confirmed that coupling bionic method can significantly improve the stubble cutting efficiency, which was a valuable contribution to the design of stubble cutting device for no-till planter.Keywords: bionics, locust mouthparts, cutting device, corn stubbleDOI: 10.25165/j.ijabe.20201301.5031Citation: Zhao J L, Guo M Z, Lu Y, Huang D Y, Zhuang J. Design of bionic locust mouthparts stubble cutting device. Int J Agric & Biol Eng, 2020; 13(1): 20–28.